Cost-benefit analysis of mangrove reforestation in Sibunag, Guimaras - Fernandez, Cheyrl Joy J.; Parreño, Paul Erwin T. (2005.)
The continuing decline of mangrove cover in Guimaras island, which was due to massive fishpond conversion; industrialization; and increased human settlements have been answered by the widespread mangrove reforestation projects in the province. These projects were found out to be beneficial, as depicted on large gap on the mangroves' overall benefits and the cost of implementation of the mangrove reforestation project. The total benefit of mangrove per hectare was estimated at PhP 1088346.25, while the cost per hectare was only PhP 54136.27. This overall benefit includes the mean willingness to conserve, amounting to PhP 142.75. The social mean WTP on the otherhand is at PhP 221622.23. It was indeed beneficial to continue the mangrovereforestation projects. There were some considerations however, in implementing these projects like the compatibility of the soil to the mangrove seedlings, and strong winds (natural hindrances).
Research Project (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Mangrove Reforestation -- Cost-Benifit Analysis -- Sunag, Guimaras